The Effect of E-Service Quality from Telkom Care Towards Indihome on Costumer Loyalty - Hakiki, Ilham; Hidayat, Anas; Muhlison, Muhammad Bakr (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2022)
This study aims to determine the effect of whether e-service quality has a positive effect on perceived value, whether perceived value has a positive effect on loyalty, whether e-service quality has a positive effect on loyalty and whether perceived value is able to mediate the relationship between e-service quality and customer loyalty in Indihome internet service. This study uses primary data obtained by distributing online questionnaires to individual customers who use Indihome services in Yogyakarta, totaling 115 respondents. The data analysis technique used to test the hypothesis in this study uses the structural equation model (SEM) method with the AMOS 22 program. The results show that E-S-Qual has a positive and significant effect on perceived value, meaning that the better E-S-Qual, the higher the customer’s perceived value. Perceived value has a positive and significant effect on customer loyalty, meaning that the higher the perceived value of the customer towards Indihome services, the higher the customer loyalty. E-S-Qual has a positive and significant effect on customer loyalty, meaning that the better E-S-Qual, the higher customer loyalty. Perceived value is a variable that significantly mediates the relationship between E-S-Qual and customer loyalty, meaning that the better the E-S-Qual, the higher the customer loyalty.